Revisiting Urban Resilience: A Review on Resilience of Spatial Structure in Urban Refugee Neighborhoods Facing Demographic Changes - Alawneh, Salwa M.; Rashid, Mahbub (Frontiers in Sustainable Cities, 2022)
Providing a durable and sustainable approach based on urban resilience is essential for solving many spatial challenges in neighborhoods with sudden refugee influxes. As refugees settle in different locations in host cities, many of these neighborhoods have high urbanization, poor infrastructure, and over-population and their conditions impact their urban stability, livability, and quality of life. Hence, this study will review the urban resilience literature focusing on a set of resilient spatial elements of a neighborhood to support the design and planning of refugee settings. First, the theories of urban resilience are reviewed to identify the characteristics of resilience and classify the reviewed literature by different focused categories of spatial resilience. Second, the resiliency of spatial structure will be explored by analyzing the links between resilient characteristics and urban form attributes at the neighborhood scale. The review summarizes a set of resilient spatial measurements by using urban form indicators of resilient characteristics facilitated by geospatial technologies. Further, a framework of resilient spatial structure in refugee neighborhoods is proposed using existing urban resilience frameworks. The proposed framework includes factors of urban form attributes at the neighborhood scales (e.g., blocks, plots, and building scale), resilience in refugee contexts, and urban resilience mechanisms. The study is not limited to providing operative resilience knowledge. It provides spatial strategies for humanitarian organizations and inter-governmental to properly contribute to the vulnerable spatial structures of refugee settings and to broaden opportunities for the assessment, profiling, communication, monitoring, and planning of resilient refugee neighborhoods.